Restoration of bighorn sheep: History, successes, and remaining conservation issues - Whiting, Jericho C.; Bleich, Vernon C.; Bowyer, R. Terry; Epps, Clinton W. (Frontiers in Ecology and Evolution, 2023)
Mammals are imperiled worldwide and exhibit downward trends in their populations and distributions. Likewise, large-bodied herbivores have undergone a collapse in numbers and are at the highest extinction risk of all mammals. Bighorn sheep (Ovis canadensis) are among those large-bodied herbivores that possess a slow-paced life history, suffer from debilitating diseases, and have experienced range contractions across their historical distribution since the late 1800s. Translocations and reintroductions of these mountain ungulates are key aspects of restoration and often are used to re-establish populations in historical habitat or to supplement declining herds. Millions of US dollars and much effort by state and federal natural resource agencies, as well as public and private organizations, have been expended to restore bighorn sheep. Despite those efforts, translocated populations of bighorn sheep have not always been successful. Because restoration is a frequently used management tool to re-establish populations, we assess this management tool to provide insights in the context of conservation of bighorn sheep. We focus briefly on past efforts to restore bighorn sheep populations and follow with updates on the value of habitat enhancements, genetic issues, the importance of ecotypic or phenotypic adaptations when restoring populations, predation, and disease transmission. We also raise issues and pose questions that have potential to affect future decisions regarding the restoration of bighorn sheep. This information will help conservationists improve the success of efforts for conserving these iconic large mammals.